The Mediating Role of Integrated Reporting: Analyzing Firm Characteristics and Performance in Malaysian Public Firms - Wisaksono, Endhyta; Md Nasir, Noorul Azwin; Jamil, Amira; Muhamad, Siti Fariha (International Journal of Research in Interdisciplinary Studies, 2025)
This study examines the mediating role of Integrated Reporting (IR) in the relationship between firm characteristics (age, leverage, and liquidity) and firm performance (Return on Equity) among Malaysian public firms. Analyzing 2022 annual and sustainability reports from 281 Bursa Malaysia-listed firms using structural equation modeling, findings show that liquidity enhances IR disclosure, while firm age negatively impacts it. Leverage positively affects IR but does not significantly influence ROE. IR significantly mediates firm characteristics and performance, reinforcing its role in transparency, accountability, and stakeholder trust. Firms with higher IR quality demonstrate superior ROE, underscoring IR’s strategic value in corporate governance and long-term profitability. This study validates IR’s role in firm performance and introduces an IR Disclosure Index as a benchmarking tool, offering insights for managers, investors, and regulators.